PENGARUH LATIHAN LEMPAR TANGKAP DAN LATIHAN LEMPAR SASARANTERHADAP KETEPATAN DAN KECEPATAN MELEMPAR BOLA PADA OLAHRAGA SOFTBALL - Ronald Dwi Ardian Fufu; Agus Hariyanto; Himawan Wismanadi; Al Ihzan Tajuddin (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
The aim of this study is to analyze and determine 1) The effect of throw and catch exercise toward the accuracy and speed to throw the ball in softball sport, 2) The effect of throw target toward throwing ball accuracy and speed in softball, 3) The effect of throw and catch exercise and throw target exercise toward accuracy and speed in throwing the ball in softball sport dan 4) Which exercise greater influence on the accuracy and speed to throw the ball in sports softball.The type of research is quantitative with a quasi-experimental methods (quasi experiment) and use matching only design as research design. The amount of research variables is , which is independent variables (throw and catch and throw target exercise) and dependent variables (accuracy and speed to throw the ball in softball sports). The amount of the sample was 32 men ​​college students of UNESA UKM softball members - Baseball drawn from the population research. The instrument used was O'Donnell Softball Test, created by O'Donnell, includes: Overhand Accuracy Throw and Speed to measure the accuracy and speed to throw the ball. The data were analyzed using paired T-test sample with the level of hypothesis rejection at the significance level of 0.05 and MANOVA (Multivariate Analysis of Variance). The results showed that: (a) The experimental group I for accuracy 3.63636 point and speed 4.00000 MPH. (B) The experimental group II for accuracy 2.18182 point and speed 2.27273 MPH. (C) The control group 's accuracy 2.00000 point and speed 2.30000 MPH. The Conclusions from the study were: 1) There is a significant effect of throw and catch exercise on accuracy and speed to throw the ball in softball sport, 2) There is a significant effect of targets the throw exercise on accuracy and speed throw the ball in softball sports, 3) There are differences in the effects of exercise throwing catch and throwing exercises targeted against the accuracy and speed to throw the ball in sports softball, 4) Throw and catch Exercise more influence on accuracy and speed to throw the ball in the softball sport.